Correlation of Amoebic form in ceramic modular sculpture / Noor Ashraf Noor Othman - Noor Othman, Noor Ashraf (2013)
Since the debut and popularization of Duchamp’s fountain, post modern and contemporary sculpture had been symbolized and identified by the nature surrounding, the effect of post-colonial and post-war mentality had altered our worldview and perception which in turn affected our sense of narratives. Postmodern visual culture lend to it a certain freedom in narratives building, unrestricted by the motives and conditions of previous visual tradition. My work deals with this sense of a narrative, which is formed and shaped not in the traditional manner, but looking to microorganisms. Rather the narratives, for the works often with the object rather than artistic intentions. This which explain my sculptures. Doing experiments to find amoebic forms and shapes for my sketches on paper and sketches on clay and other material, which is guides my artistic decision which the similarity and juxtapositions of Amoebic form. Sculptures is an aspects in art that can connect people to the artwork such as the interaction from the idea of composition setting, the manipulation of space in terms of artworks presentation, and the knowledge of materials which sometimes involves everyday objects. My sculpture tends to focus on the amoebic forms and characters which leads to concept in developing the modular system in a sculpture methods. I am using clays, paper clays, cements, and plasters as my main materials because of my personal interests and specialization. These materials have their own characteristic which are relative to my sculpture contents. On the formal level, my work is constructed by assembling and manipulating these materials to create Amoebic forms with metaphorically within a historic assembling style. In my journal, I would attempt to explain my inspiration and the aesthetic decision that lead me to my works. The progress of the works would also be documented and all observation are explained in this decantation.